High density polyethylene (HDPE) microplastics impair development and swimming activity of Pacific oyster D-larvae, Crassostrea gigas, depending on particle size. (May 2020) - Bringer, Arno; Thomas, Hélène; Prunier, Grégoire; Dubillot, Emmanuel; Bossut, Noémie; Churlaud, Carine; Clérandeau, Christelle; Le Bihanic, Florane; Cachot, Jérôme
Abstract: Understanding the effects of plastic debris on marine ecosystems is essential in encouraging decision-makers to take action. The present study investigates the effect of a 24 h experimental exposure to high density polyethylene (HDPE) microplastics (MPs) of different sizes (4–6, 11–13 and 20–25 μm) and at three concentrations (0.1, 1 and 10 mg MP.L −1 ) on the development and locomotor activity of early stages of Pacific oyster, Crassostrea gigas . The bivalve embryo-larval assay (NF ISO 17244, 2015) was used in this study but with additional toxicity criteria: developmental arrests, abnormal D-larvae, maximum speed and swimming trajectory. Copper (Cu), was used as a positive control. Our results show that smaller MPs (4–6 and 11–13 μm) induced higher rates of malformations and developmental arrests than the larger ones (20–25 μm). In addition, a dose-dependent decrease of maximum swimming speed was observed for larvae exposed to MPs of 4–6 and 11–13 μm. On the other hand, there was no significant difference in swimming speed with the largest MPs size tested (20–25 μm). For all three sizes of MPs, there was a decrease in straight-line swimming trajectories, and an increase in circular trajectories. This abnormal swimming behaviour could affect larvae survival as well as colonization of new habitats. Graphical abstract: Image 1 Highlights: Oyster embryos were exposed for 24 h to different sizes of HDPE microplastics. HDPE MPs bind to locomotor eyelashes of oyster D-larvae. HDPE MPs affect swimming activity and development of oyster D-larvae. Smaller HDPE MPs are more toxic to oyster D-larvae. Abstract : Polyethylene microplastics of different sizes induce differential deleterious effects on development and swimming activity of oyster D-larvae.